INTEGRATING ESG METRICS INTO TRADITIONAL ACCOUNTING SYSTEMS: A FRAMEWORK FOR FUTURE PRACTICE - Ia Kurnia; Ari Purwanti; Loso Judijanto; Aspiati A. Samiun; Dian Saripujiana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The integration of Environmental, Social, and Governance (ESG) metrics into traditional accounting systems has emerged as a critical area of focus for modern businesses aiming to balance financial performance with sustainable and ethical practices. This paper provides a comprehensive literature review on the evolution of ESG metrics and their relevance in accounting frameworks. Through the analysis of recent studies, it explores the challenges and opportunities associated with incorporating ESG factors into conventional accounting systems, including the impact on financial reporting, stakeholder engagement, and regulatory compliance. The review highlights key frameworks that have been proposed for integrating ESG into financial disclosures, such as the Global Reporting Initiative (GRI) and the Sustainability Accounting Standards Board (SASB). Furthermore, it examines how ESG integration can enhance corporate transparency, improve risk management, and align with long-term strategic goals. The paper concludes by proposing a framework for the future practice of ESG integration in accounting, outlining key areas for further research and development.